DIPLOMASI EKONOMI INDONESIA DALAM MENINGKATKAN EKSPOR SEPATU DI PASAR EFTA (EUROPEAN FREE TRADE ASSOCIATION) PERIODE 2017-2021 - Hildatul Jannah, (2022)
The purpose of this study is to analyze Indonesia's economic and diplomatic strategy for exporting shoes to EFTA according to the Indonesia-EFTA Comprehensive Economic Partnership Agreement (IE-CEPA). This study uses qualitative methods and economic diplomacy and free trade theory as analytical tools. Indonesia's economic diplomacy strategy is to use market research and trade promotion at various forums and conferences as a place to assert national interests. The results of this study show that Indonesia was unable to maximize its potential for cooperation with the EFTA. Indonesia needs to reconsider some barriers to the country's footwear industry to boost footwear exports to potential markets through free trade agreements. Keywords: Economic Diplomacy, Indonesia, EFTA, Footwear Export